(10/4x)+3=2x-3

Simple and best practice solution for (10/4x)+3=2x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (10/4x)+3=2x-3 equation:



(10/4x)+3=2x-3
We move all terms to the left:
(10/4x)+3-(2x-3)=0
Domain of the equation: 4x)!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
(+10/4x)-(2x-3)+3=0
We get rid of parentheses
10/4x-2x+3+3=0
We multiply all the terms by the denominator
-2x*4x+3*4x+3*4x+10=0
Wy multiply elements
-8x^2+12x+12x+10=0
We add all the numbers together, and all the variables
-8x^2+24x+10=0
a = -8; b = 24; c = +10;
Δ = b2-4ac
Δ = 242-4·(-8)·10
Δ = 896
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{896}=\sqrt{64*14}=\sqrt{64}*\sqrt{14}=8\sqrt{14}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(24)-8\sqrt{14}}{2*-8}=\frac{-24-8\sqrt{14}}{-16} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(24)+8\sqrt{14}}{2*-8}=\frac{-24+8\sqrt{14}}{-16} $

See similar equations:

| 6x+2+5x+9=15x-21 | | 10/4x+3=2x-3 | | -7y-4-9=18 | | |-7a-10|=-10a | | 44w-18=41w | | 2(5x-1)=24x-7(2x+1) | | 2–4p=–4–6p | | -9x-7(x-5)=-8(x-8)+3 | | 9x-7x-5=-19 | | r+3=21 | | h=1/3=5/3 | | 3(3a-3)-9=81 | | x-0.3=7 | | P=32x-0 | | 8(x+1)+3=-5(x+5) | | 14=22+x;8 | | 2z+7-5=-30 | | N-11n=0-10 | | t/4+8=12 | | 3,14x^2-14x-147=0 | | -2+5x-3-2x=-2x+5+3x | | .2x+625000=x | | 12=3(-x+1 | | x-20=(800/X)+2X-20 | | 5r^2-100=0 | | ​3​​4​​=−6e−​3​​5​​ | | 6a-a-a=4a | | x+2+5x=9+4x-1 | | -11x+7x+1=9 | | 70=-7(2-2z | | 1/2y+5-3/4=0 | | (7x-4)^2+16=0 |

Equations solver categories